IMPLEMENTASI PROGRAMKELUARGA HARAPAN (PKH) DALAM PERANTARA KEMISKINAN DI DESA BANDAR SETIA KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Latifah Hanum, Zainuddin Nasution, (Fakultas Agama Islam, 2022)
The Family Hope Program (PKH) is one of the policies of the government that can help reduce poverty in Indonesia, where in this Harahap Family Program the target is KPM (Beneficiary Group). assistance from PKH, with the requirements that the KPM must fulfill the obligations that have been regulated and stipulated in the general PKH guidelines related to improving human resources (Human Resources). In the short term, PKH aims to reduce the free expenditure of poor families and in the long term, PKH is a program that is expected to break the poverty chain between generations and is also expected to improve the quality of human resources in the fields of education, health and social welfare. This study aims to determine the process of implementing the Family Hope Program (PKH) in Bandar Setia village, Percut Sei Tuan sub-district and to describe the obstacles in implementing PKH in this village. The method used in this research is descriptive qualitative research method with data collection techniques through interviews, observation and literature study. Based on the results of the study, it was shown that in general the process of implementing the PKH program in Bandar Setia village, Percut Sei Tuan sub-district, was quite good. This can be seen from every stage of the implementation process that went well and smoothly, although here and there there are still some shortcomings, but overall the goals and objectives of this PKH have been achieved well.